Virtual screening stategies in drug discovery – A brief overview - Long, Pham Quoc; Quan, Pham Minh (Vietnam Journal of Science and Technology, 2021)
Computer-aided drug design has now become a compulsory tool in the drug discovery and development process which uses computational approaches to discover potential compounds with expected biological activities. Firstly, this review provides a comprehensive introduction of the virtual screening technique, knowledge and advances in both SBVS and LBVS strategies also presented. Secondly, recent database of compounds provided worldwide and drug-like parameters which are helpful in supporting the VS process will be discussed. These information will provides a good platform to estimate the advance of applying these techniques in the new drug-lead identification and optimization.